Two-photon vibrational spectroscopy for biosciences based on surface-enhanced hyper-Raman scattering - Kneipp, Janina (National Academy of Sciences, 2006)
Two-photon excitation is gaining rapidly in interest and significance in spectroscopy and microscopy. Here we introduce a new approach that suggests versatile optical labels suitable for both one- and two-photon excitation and also two-photon-excited ultrasensitive, nondestructive chemical probing. The underlying spectroscopic effect is the incoherent inelastic scattering of two photons on the vibrational quantum states called hyper-Raman scattering (HRS). The rather weak effect can be strengthened greatly if HRS takes place in the local optical fields of gold and silver nanostructures. This so-called surface-enhanced HRS (SEHRS) is the two-photon analogue to surface-enhanced Raman scattering (SERS). SEHRS provides structurally sensitive vibrational information complementary to those obtained by SERS. SEHRS combines the advantages of two-photon spectroscopy with the structural information of vibrational spectroscopy and the high-sensitivity and nanometer-scale local confinement of plasmonics-based spectroscopy. We infer effective two-photon cross-sections for SEHRS on the order of 10(−46) to 10(−45) cm(4)·s, similar to or higher than the best “action” cross-sections (product of the two-photon absorption cross-section and fluorescence quantum yield) for two-photon fluorescence, and we demonstrate HRS on biological structures such as single cells after incubation with gold nanoparticles.